'I know how it works!' student engagement with exhibits in a science museum. Issue 3 (3rd July 2019) - Shaby, Neta; Assaraf, Orit Ben-Zvi; Tal, Tali
ABSTRACT: This research examines the same 12 school-students making repeat visits over a three-year-period to a science museum. We used a qualitative approach,  analysing video recordings of museum visit and interviews with students, focusing on the way students use their former engagement in a science museum using a retrospective view that can offer insight into the pedagogy of the visit and exhibit design. The significance of this study lies in its retrospective lens that allowed us to understand how students build on earlier engagement with museum exhibits when they make repeat visits to informal learning environments. Our retrospective analysis of student learning from five exhibits suggests certain pedagogical and facilitation strategies in three specific areas: first, the sensory-motor experience promotes students' understanding of the scientific principle of the exhibit. Second, exhibits should aim at presenting abstract concepts in a tangible way. Third, museum educators should use anchor-points throughout the visit to create a more cohesive 'story' for students, so that they relate to it in a way, which will help them remember the experience over time. Consequently, the main implications of this study concern exhibit design and the overall pedagogy of the visit.